On the Stability of Hybrid Polycycles - Santana, Paulo [UNESP]; Serantola, Leonardo [UNESP] (Springer Nature, 2025)
In this paper we provide the stability of generic polycycles of hybrid planar vector fields, extending previous known results in the literature. The polycycles considered here may have hyperbolic saddles, tangential singularities and jump singularities.
Keywords: Graphics of a vector field; Hybrid dynamical systems; Polycycles; Singular cycles